Causal Modeling of Psychological Success in Work Organizations - Griffin, Larry J. (Academy of Management Journal, 1977)
This paper demonstrates the applicability of path analysis to the study of psychological success in work organizations by reanalyzing three previously published studies. Two examples test and estimate two causal models of psychological success. The final example demonstrates that the utility of path analysis is dependent upon adequate theoretical formulation.